Information and Communication Technology (ICT) Pedagogical Competency of Technology and Livelihood Education (TLE) Teachers in a Non-Urban Public School - Biray, Ersyl T.; Gumban, James R.; Martirez, Amzi V. (Future Science / FSH-PH Publications, 2024)
Outcomes-based education is practiced in Philippine schools to turn out skilled manpower for the global market. Accordingly, technology teachers are expected to be technically competent in the area assigned to deliver and carry out teaching tasks as, highly qualified teachers produce skilled learners. How well have educational agencies prepared these teachers in rural areas is worth looking into. Thus, this study tried to establish the information and communication technology (ICT) pedagogical competency of Technology and Livelihood Education (TLE) teachers in a non-urban school in the Division of Aklan. Thirty-two TLE teachers were involved as participants, and their ICT pedagogical competency was measured through the standardized questionnaire adopted from the National ICT Competency Standard Framework (NICS) for teachers. From the pretest results, five teachers who obtained basic competency levels were selected as teacher-beneficiaries of the ICT enhancement intervention program. After the intervention, the ICT pedagogical competencies from which teachers were initially found to have basic and intermediate competency levels have improved. Moreover, it was found that there was a significant difference between TLE teachers’ ICT pedagogical competence with teachers’ length of service, number of ICT training attended, and specialization. Given these results, TLE teachers in non-urban public schools in Aklan should be provided with professional development programs to sustain and improve their skills and competencies by effectively using technology in the teaching and learning processes.